Gelagat pembelian barang cetak rompak: Kesan faktor harga dan pendidikan - Lim, Hock Eam; Abdullah, Hussin (Penerbit Universiti Kebangsaan Malaysia, 2004)
This research study about the influence of price factor and education into the VCD/CD pirates purchase behavior of Kedah with Tobit model which estimated this research show that the low price of VCD/CD pirates is the main attraction. But, this price factor earn that is not significant in the quantity of VCD/CD pirates purchase.The education level shows the positive effect on the quantity of VCD/CD pirates that have been bought. This result means that the problem of VCD/CD pirates purchase is not about do not have enough knowledge, but is about insufficient in copyright or paten appreciation. This research also shows that it has writing in the sum of education level. In the effort to solve the problem of VCD/CD pirates, this research suggest the strategy to build market level for the original of VCD/CD control the maximum price and enforce tha law onto the buyer.